Synthesizing Islamic Educational Philosophy: From Al-Ghazali’s Tazkiyah Nafs to Fazlur Rahman’s Double Movement in Indonesia’s Digital Era - Putri, Lasmi Anisa; Samad, Duski; Firdaus, Firdaus (Unisia, 2025)
This article examines the urgent need for a holistic philosophy of Islamic education capable of responding to moral, intellectual, and social challenges in Indonesia’s digital era. It aims to construct an integrative educational framework by synthesizing classical Islamic educational thought with contemporary reformist approaches, focusing particularly on Al-Ghazali’s concept of tazkiyah nafs and Fazlur Rahman’s double movement methodology. Employing qualitative library research, the study analyzes primary philosophical texts and key secondary literature through thematic content analysis, comparative interpretation, and conceptual synthesis, allowing classical and modern perspectives to be read dialogically and contextualized within current educational realities. The findings demonstrate that each thinker contributes a distinct but complementary dimension: Al-Ghazali emphasizes spiritual purification and moral formation; Ibn Sina highlights systematic intellectual development; Ibn Rushd advances the harmony of reason and revelation; Ibn Khaldun situates education within social and civilizational dynamics; and Fazlur Rahman provides a methodological bridge for reinterpreting Islamic ethical principles in contemporary contexts. Their synthesis results in a holistic epistemological model integrating textual reasoning, rational inquiry, and spiritual intuition, grounded in the objectives of Islamic law. The discussion shows that this model offers practical implications for curriculum design, teacher roles, and ethical engagement with digital technology, including responses to radicalism, moral erosion, and artificial intelligence. The study concludes that a synthesized philosophy of Islamic education can serve as a viable foundation for revitalizing Islamic education in Indonesia, fostering spiritually grounded, intellectually critical, and socially responsible learners in the digital age